2020
DOI: 10.1002/pat.5052
|View full text |Cite
|
Sign up to set email alerts
|

Meso research on the fiber orientation distribution of aramid fiber‐reinforced rubber composite

Abstract: Aramid fiber-reinforced rubber composites (AFRCs) have attracted considerable attention due to their excellent mechanical properties. These mechanical properties provide the composites with a certain degree of anisotropy due to the fiber orientation distribution (FOD) in the AFRCs, thereby allowing them to flexibly meet requirements based on different scenarios. However, the quantitative determination of FOD in AFRCs continues to be a challenge. In this study, the triple ion-beam cutting technique was proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Heller et al 29 found a similar result.) Furthermore, it is well known that highly oriented fibers in samples can result in anisotropic mechanical properties, 30,31 so different printing directions that orient fibers in different directions significantly affect mechanical properties of the material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heller et al 29 found a similar result.) Furthermore, it is well known that highly oriented fibers in samples can result in anisotropic mechanical properties, 30,31 so different printing directions that orient fibers in different directions significantly affect mechanical properties of the material.…”
Section: Resultsmentioning
confidence: 99%
“…Heller et al 29 found a similar result.) Furthermore, it is well known that highly oriented fibers in samples can result in anisotropic mechanical properties, 30,31 so different printing directions that orient fibers in different directions significantly affect mechanical properties of the material. These differences in compressive behavior could be attributed to the different direction of short fibers in specimens printed in different printing directions as described previously.…”
Section: Morphological Properties Of Printed Compositesmentioning
confidence: 99%